2022
DOI: 10.1108/jd-12-2021-0245
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale analysis of query logs to profile users for dataset search

Abstract: PurposeWith an explosion of datasets available on the Web, dataset search has gained attention as an emerging research domain. Understanding users' dataset behaviour is imperative for providing effective data discovery services. In this paper, the authors present a study on users' dataset search behaviour through the analysis of search logs from a research data discovery portal.Design/methodology/approachUsing query and session based features, the authors apply cluster analysis to discover distinct user profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Their experimental results showed that proficient searchers built task outcomes with higher quality. Similar observations were also made in [42] by J Mao et al In addition to the quality of task outcome, the relation between searchers' proficiency and other search behaviors was also investigated in [43][44] [45]. The search behaviors investigated in these studies include the amount of query words, the length of sessions, the quality of query words, and searchers' judgement on the relevance of search results.…”
Section: H Comparasions With Other Approachesmentioning
confidence: 74%
“…Their experimental results showed that proficient searchers built task outcomes with higher quality. Similar observations were also made in [42] by J Mao et al In addition to the quality of task outcome, the relation between searchers' proficiency and other search behaviors was also investigated in [43][44] [45]. The search behaviors investigated in these studies include the amount of query words, the length of sessions, the quality of query words, and searchers' judgement on the relevance of search results.…”
Section: H Comparasions With Other Approachesmentioning
confidence: 74%
“…Our research methodology is user-centric and we analyze systems based on the outcomes and benefits of ELK and GR for decision makers. Understanding users' dataset behavior is essential to providing effective data discovery services [12]. From the search for predecessors, the analysis of log files has developed a variety of methods that efficiently determine contextualized answers to user needs.…”
Section: Research Methodology and Approachmentioning
confidence: 99%
“…We chose these query-level features based on prior findings by Kathuria et al (2010), who defined query intent using query-level features, such as query length and reformulation strategy. We also based our feature selections on work by Sharifpour et al (2022), who proposed distinct user groups by performing hierarchical clustering on query logs (2022). We selected these categories based on their relevance to differentiating user behavior and profiling users based on their web queries.…”
Section: Feature Selectionmentioning
confidence: 99%